Electron Microbursts Induced by Nonducted Chorus Waves - Chen, Lunjin; Zhang, Xiao-Jia; Artemyev, Anton; Zheng, Liheng; Xia, Zhiyang; Breneman, Aaron W.; Horne, Richard B. (Frontiers in Astronomy and Space Sciences, 2021)
Microbursts, short-lived but intense electron precipitation observed by low-Earth-orbiting satellites, may contribute significantly to the losses of energetic electrons in the outer radiation belt. Their origin is likely due to whistler mode chorus waves, as evidenced by a strong overlap in spatial correlation of the two. Despite previous efforts on modeling bursty electron precipitation induced by chorus waves, most, if not all, rely on the assumption that chorus waves are ducted along the field line with zero wave normal angle. Such ducting is limited to cases when fine-scale plasma density irregularities are present. In contrast, chorus waves propagate in a nonducted way in plasmas with smoothly varying density, allowing wave normals to gradually refract away from the magnetic field line. In this study, the interaction of ducted and nonducted chorus waves with energetic electrons is investigated using test particle simulation. Substantial differences in electron transport are found between the two different scenarios, and resultant electron precipitation patterns are compared. Such a comparison is valuable for interpreting low Earth-orbiting satellite observations of electron flux variation in response to the interaction with magnetospheric chorus waves.